NOMOR INDUK BERUSAHA SEBAGAI LEGALITAS BAGI PELAKU UMKM DESA TAWAR KABUPATEN MOJOKERTO - Widarsadhika, Rahadyan; Ulfa, Siti Maria; Fauzi, Muhammad Thoriq; Suluh Putri, Katarina Kristi (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting regional economic growth, particularly in the aftermath of the COVID-19 pandemic. One concrete manifestation of governmental assistance is the implementation of Government Regulation Number 24 of 2018, which introduces the Online Single Submission (OSS) platform to streamline the licensing process, specifically in obtaining the Business Identification Number. Through OSS, the licensing procedure becomes more efficient, rapid, and transparent. The adoption of OSS aims not only to provide convenience for business entities but also to bolster investment in the MSME sector. It is recommended to enhance the comprehension of business stakeholders through additional training and awareness initiatives to fortify business legitimacy, foster MSME expansion, and generate positive effects on local economic development. The methods utilized for activity execution encompass lectures, discussions, and practical sessions, targeting micro, small, and medium-sized enterprises situated in Tawar Village, Mojokerto Regency. This endeavor has been effectively carried out, resulting in a notable increase in the successful registration of Business Identification Numbers (NIBs).